Tall buildings : study of effectiveness of linked slab as rigid diaphragm in multi-tower building - Wang, Xiaowei (2014)
The Singapore mainland area measures about 580m2. With 5 million people living there, the average density is more than 7000 people/km2. This makes of Singapore the second most densely populated country worldwide. The main problem is based on limited space of Singapore Island on which buildings and infrastructures are already overdeveloped. One of the solutions is to construct higher residential and commercial buildings. However, tall buildings are highly prone to strong gusts of wind and ground tremors which impose considerable tension and compression forces on the structures.